Legislative regulation of linguistic relationships in Ukraine - Makarets, Iuliya (Current issues of Ukrainian linguistics: theory and practice, 2019)
The article focuses on the issue of legislative regulation of linguistic relationships in Ukraine. The ability of a national language to function as a means of consolidation and national identification depends to a large extent on state linguistic policy, political support that the language receives. The state legislation on language is indicative in this regard while it establishes the status of languages, the linguistic model and the linguistic regime. In accordance with the Constitution of Ukraine, the Ukrainian language is a state language in Ukraine. The dynamics of the Ukrainian legislation on languages illustrates the inconsistency of the implementation of this constitutional norm. The article analyzes the milestones of its formation. The content of the basic laws in the sphere of linguistic relationships (Law of the USSR ‘On Languages in the Ukrainian SSR’ (1989), the Law of Ukraine ‘On the Principles of the State Language Policy’ (2012), which is invalid now, and the new Law of Ukraine ‘On the Functioning of the Ukrainian Language as a State Language’ (2019)), the socio-political tendencies, that preceded their adoption, their evaluation by tpublic and world community as well as their consequences for linguistic situation in Ukraine are described. The possibility of official bilingualism approving is studied. The article analyzes historical, cultural and political preconditions for the adoption of official bi- or multilingualism by other states, acceptability of this linguistic model for Ukraine and possibility to overcome existing linguistic contradictions.
Keywords: national language, official (state) language, regional language, linguistic relationships, legislation on languages, linguistic policy.